2014
DOI: 10.1016/j.neubiorev.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain systems underlying the affective and social monitoring of actions: An integrative review

Abstract: (max 170 words)Action monitoring allows the swift detection of conflicts, errors, and the rapid evaluation of outcomes. These processes are crucial for learning, adaptive behavior, and for the regulation of cognitive control. Our review discusses neuroimaging and electrophysiological studies that have explored the contribution of emotional and social factors during action monitoring. Metaanalytic brain activation maps demonstrate reliable overlap of error monitoring, emotional, and social processes in the dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
160
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 226 publications
12
160
2
Order By: Relevance
“…In the present context, conflict monitoring signals have been observed in several brain regions classically implicated in emotion, such as the amygdala (Koban & Pourtois, 2014;Pourtois et al, 2010) and The Emotive Nature of Conflict 16 anterior insula (Klein et al, 2007;Ullsperger, Harsay, Wessel, & Ridderinkhof, 2010).…”
Section: The Neural Integration Of Control and Emotionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the present context, conflict monitoring signals have been observed in several brain regions classically implicated in emotion, such as the amygdala (Koban & Pourtois, 2014;Pourtois et al, 2010) and The Emotive Nature of Conflict 16 anterior insula (Klein et al, 2007;Ullsperger, Harsay, Wessel, & Ridderinkhof, 2010).…”
Section: The Neural Integration Of Control and Emotionmentioning
confidence: 75%
“…Rather than assuming that the brain "knows" when to exert control, these models specify the processes that detect the The Emotive Nature of Conflict 8 fluctuating need for control in mathematically tractable terms (Danielmeier, Wessel, Steinhauser, & Ullpserger, 2009;Yeung et al, 2004). In parallel to these accounts, however, affective neuroscience has revealed that conflict elicits many of the hallmark features of emotion, including valence judgements, physiological arousal, and subjective emotional experiences (Dreisbach & Fisher, 2015;Etkin, Egner, & Kalisch, 2012;Inzlicht, Bartholow, & Hirsh, 2015;Koban & Pourtois, 2014;Pessoa, 2009;Shackman et al, 2011), proposing a degree of integration between control and emotion that is virtually ignored by computational accounts.…”
Section: Neural Conflict Monitoring and Cognitive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a series of studies by Pourtois (2012, 2013) went beyond earlier findings by showing that dedicated internal monitoring systems enable individuals to rapidly tag 6 tension elicited by clear and current threats. Noteworthy, Moser et al (2013) provided evidence for an association between anxious apprehension (worry) and an enhanced ERN component, with no such link found with anxious arousal, suggesting that worry (but not arousal) might actually play a predominant role in abnormal early error monitoring processes typically observed in high anxious individuals Koban & Pourtois, 2014). An older dominant model accounting for modulatory effects of anxiety on cognition stated that worry might reflect the occupation (or hijacking) of resources that would otherwise be allocated to the control of attention (M. W. Eysenck, 1979).…”
Section: Introductionmentioning
confidence: 97%
“…This kind of blurring of the traditional (antagonistic) boundaries between emotional and cognitive processes has gained more and more influence in the behavioral and neural sciences (3,4). For example, a recent overview of neuroimaging and electrophysiological studies shows a substantial overlap of error monitoring and emotional processes in the dorsal mediofrontal cortex, lateral prefrontal areas, and anterior insula (5,6). A consequence of this emerging integrative view is that emotional states and signals should be monitored in the same way as other intentional actions.…”
mentioning
confidence: 99%